2019
DOI: 10.1016/j.vaccine.2019.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Differential durability of immune responses to measles and mumps following MMR vaccination

Abstract: The development and widespread use of mumps vaccine resulted in a dramatic and sustained decrease in the incidence of mumps disease; however, since 2000, an increase in the size and number of mumps outbreaks in the United States and other countries has sparked renewed interest in the durability of mumps-specific immunity elicited by mumps vaccination. The most likely explanation for mumps cases in previously immunized persons may be secondary vaccine failure, or waning immunity. In the current study, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
5
36
0
1
Order By: Relevance
“…Also, our results showed a similar distribution of anti-measles IgG among different age groups as shown by Ristic et al [13]. Here, we observed the same trend of decreasing measles-specific IgG titer over time from vaccination, as reported by Kennedy et al [7]; however, there was a longer time between possible vaccination and serological test in our study (up to 40 vs. 17 years). Our results are consistent with those obtained by Coppeta et al who showed that total seropositivity reached 87% in a group of adult hospital employees, with the highest ratio in a group of patients not vaccinated in childhood (born before 1982) and lowest in the group born in 1992-1999 [1].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, our results showed a similar distribution of anti-measles IgG among different age groups as shown by Ristic et al [13]. Here, we observed the same trend of decreasing measles-specific IgG titer over time from vaccination, as reported by Kennedy et al [7]; however, there was a longer time between possible vaccination and serological test in our study (up to 40 vs. 17 years). Our results are consistent with those obtained by Coppeta et al who showed that total seropositivity reached 87% in a group of adult hospital employees, with the highest ratio in a group of patients not vaccinated in childhood (born before 1982) and lowest in the group born in 1992-1999 [1].…”
Section: Discussionsupporting
confidence: 92%
“…Measles virus infection causes life-long protective immunity, while two doses of MMR vaccine should also provide appropriate immunization [3]. However, there are some reports suggesting that the immune response to measles following MMR vaccination provides less-sufficient immunization and that the amount of specific anti-measles immune antibodies (IgG class) decreases over time [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We noted that 23% of the subjects who received two doses of measles vaccine did not show IgG response, similarly to those receiving only one dose of vaccine (25%) (Figure 1). This percentage appeared higher than that reported by other authors [17,20,32,33], thus, it is advisable to monitor the immune status of vaccines 10-15 years since vaccination, in order to evaluate the immune protection against measles and, eventually, implement a possible prophylactic Vaccines 2020, 8, 66 9 of 12 measure. On the other hand, a long-term high rate of seropositivity persisted after natural infection; indeed, subjects enrolled in this study who reported measles infection history were all seropositive.…”
Section: Discussionmentioning
confidence: 74%
“…Since previous studies reported that the measles protective antibody titer was decreasing over time after the administration of the second dose of MMR vaccine [17][18][19][20][21], our aim was to evaluate this phenomenon in our cohort. The vaccinated subjects (110) were divided into three groups, on the basis of the time elapsed since the administration of the second dose of vaccine: eleven years (35 subjects), 12-14 years (39 subjects) and ≥15 years (36 subjects).…”
Section: Decline Of Neutralizing Ab Titersmentioning
confidence: 99%
See 1 more Smart Citation